Complete Intraluminal Migration of Surgical Sponge (Gossypiboma) With Complete Intestinal Obstruction (KYAMC Journal, 2017)
A 33 years aged gentle lady presented with the features suggestive of acute intestinal obstruction due to complete intraluminal migration of a laparotomy sponge, five years after open cholecystectomy in a private clinic. Contrast enhanced CT scan of whole abdomen revealed an elongated intraluminal mass in the distal ileum causing intestinal obstruction. Exploratory laparotomy revealed circumvented loop of ileum with intraluminal mass sized around 6x12 cm in the terminal ileum. Enterotomy delivered a surgical sponge with no external or internal communication. Though intraluminal migration of retained surgical sponge has often been reported. But complete migration with features of intestinal obstruction is rare.KYAMC Journal Vol. 4, No.-1, July 2013, Page 362-365